Impact of Iron and Magnesium on Microalgae Growth from a Comparative Life Cycle Assessment Perspective - Canci, Baris; Kosma, Elvan Burcu; Demirbay, Tugba; Manav-Demir, Neslihan; Ozkaya, Bestami; Gunes, Serap (SPRINGER INT PUBL AG, 2025)
In this study, the effect of Blue Green-11 (BG-11) growth medium with different iron (Fe) and magnesium (Mg) concentrations on chlorophyll-a concentration in microalgae (Chlorella vulgaris sp. and Spirulina platensis sp.) was investigated. The maximum chlorophyll-a concentration was measured 20.47 mg/L for Chlorella vulgaris sp. when Fe and Mg concentrations were 0.4 and 8 mM, respectively, and 11.01 mg/L for Spirulina platensis sp., when 0.01 and 0.3 mM, respectively. In addition, in the study, a Life Cycle Assessment (LCA) was conducted on microalgae cultivated in BG-11 media containing different concentrations of Fe and Mg. The results were compared. The process was determined to have the greatest environmental impacts in terms of Human Carcinogenic Toxicity, Freshwater Eutrophication, Marine Ecotoxicity, Freshwater Ecotoxicity and Fine Particulate Matter Formation. Finally, a scale-up was applied for microalgae production and harvest, and its impact on the environment was evaluated in comparison with laboratory scale using Life Cycle Assessment.
Keywords: Microalgae; Chlorophyll; Harvesting; Life Cycle Assessment (LCA); BIODIESEL PRODUCTION; CULTIVATION; SCALE; ALGAE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources